RELATED LIVER TRANSPLANTATION IN THE REPUBLIC OF UZBEKISTAN: CURRENT STATE AND DEVELOPMENT PROSPECTS (Herald of the National Children's Medical Center, 2024)
Transplantation is the only radical treatment for end-stage liver diseases. The improvement of liver transplant results directly depends on the training of recipients, careful selection of donors, surgical techniques and rehabilitation methods in the postoperative period. Despite the positive results achieved in the survival of recipients after transplantation, the incidence of complications is still high, which requires further research in this direction.